2020
DOI: 10.3390/ijms21072454
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Human Nav1.2 Resurgent and Persistent Sodium Currents by Cannabidiol and GS967

Abstract: Many epilepsy patients are refractory to conventional antiepileptic drugs. Resurgent and persistent currents can be enhanced by epilepsy mutations in the Nav1.2 channel, but conventional antiepileptic drugs inhibit normal transient currents through these channels, along with aberrant resurgent and persistent currents that are enhanced by Nav1.2 epilepsy mutations. Pharmacotherapies that specifically target aberrant resurgent and/or persistent currents would likely have fewer unwanted side effects and be effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…The conclusion that CBD prevents the opening of Nav channels is further affirmed by the observation of CBD's inhibition of resurgent currents in Nav1.2 and Nav1.6 (Ghovanloo and others 2018c; Mason and Cummins 2020;Patel and others 2016). CBD also does not alter the open state fast inactivation time constants of neuronal Nav channels, suggesting that it does not interact with the sodium conduction pathway when the channel is open.…”
Section: Cbd Is An Inhibitor Of Voltage-dependent Sodium Currentsmentioning
confidence: 88%
“…The conclusion that CBD prevents the opening of Nav channels is further affirmed by the observation of CBD's inhibition of resurgent currents in Nav1.2 and Nav1.6 (Ghovanloo and others 2018c; Mason and Cummins 2020;Patel and others 2016). CBD also does not alter the open state fast inactivation time constants of neuronal Nav channels, suggesting that it does not interact with the sodium conduction pathway when the channel is open.…”
Section: Cbd Is An Inhibitor Of Voltage-dependent Sodium Currentsmentioning
confidence: 88%
“…Interestingly, several compounds exist that have been shown to selectively target pathological currents produced by Na v 1.6. For instance, cannabidiol and GS967 (otherwise known as Prax330) have been shown to preferentially reduce aberrant persistent and resurgent currents over transient sodium currents, however these compounds do not appear to be selective for Na v 1.6 and can target currents in other isoforms, like Na v 1.2 [ 91 , 114 , 115 , 116 ]. More recently, anti-epileptic compound screens in zebrafish models of epilepsy revealed two novel blocking compounds, MV1312 and MV1369 [ 117 ].…”
Section: Na V 16 Overviewmentioning
confidence: 99%
“…A previously study demonstrated that CBD at 1μM inhibit preferably resurgent currents than transient current in Nav1.6 WT and also inhibit peak resurgent current in Nav1.6 mutant N1768D, with less effect in current density and without alters voltage dependence of activation ( Patel et al., 2016 ) Possibly the modulation of CBD over mutations in SCN8A that promotes a phenotype with increased resurgent currents would cause a reduction in the causative excitability of epileptic seizures. CBD also showed its ability to preferential inhibit resurgent currents in the NaV1.2 channel ( Mason and Cummins, 2020 ). Due the role of Nav1.2 and Nav1.6 in excitatory neurons, preferentially inhibition in resurgent currents by CBD could possibly reduce the excitability in that subset of neurons and decrease the frequency of seizures by a change in threshold of activation and repetitive fire ( Lewis and Raman, 2014 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%